Artificial intelligence techniques applied to dynamic security assessment of isolated systems with high wind power penetration - N. Hatziargyriou (2000)
In this paper the application of ArtificialIntelligence to on-line dynamic security assessment ofisolated power systems with increased wind powerpenetration is presented. The developed securityfunctions have been integrated in the dynamic securityassessment module of the advanced control system ofthe island of Crete providing timely warning of insecureoperating conditions with very satisfactory accuracy.